2017
DOI: 10.20517/2573-0002.2017.08
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between salivary cortisol levels and Hospital Anxiety and Depression scores in oral lichen planus and recurrent aphthous stomatitis

Abstract: Aim:The aim of this study was to estimate the salivary cortisol levels in patients with oral lichen planus (OLP) and recurrent aphthous stomatitis (RAS) and to correlate it with their psychological profile using the Hospital Anxiety and Depression (HAD) scale. Methods: The study population comprised of 60 patients -20 with OLP, 20 with RAS and 20 healthy controls. Salivary cortisol levels were assessed using the chemiluminescent immuno assay technique. Anxiety and depression levels were evaluated using the HAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 23 publications
(63 reference statements)
1
14
0
Order By: Relevance
“…Although the present study found no significant difference in salivary level of cortisol among the three groups, this value was the highest in the erosive OLP group, compared with the control group (1.09 vs. 0.98 mg/dL). Vassandacoumara and Daniel reported that salivary level of cortisol in OLP patients was insignificantly higher than that in healthy controls, which was similar to the present findings [19]. Shetty et al found significantly higher serum level of cortisol in erosive OLP patients compared with controls while the difference in this regard was not significant between reticular OLP patients and controls [14].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the present study found no significant difference in salivary level of cortisol among the three groups, this value was the highest in the erosive OLP group, compared with the control group (1.09 vs. 0.98 mg/dL). Vassandacoumara and Daniel reported that salivary level of cortisol in OLP patients was insignificantly higher than that in healthy controls, which was similar to the present findings [19]. Shetty et al found significantly higher serum level of cortisol in erosive OLP patients compared with controls while the difference in this regard was not significant between reticular OLP patients and controls [14].…”
Section: Discussionsupporting
confidence: 89%
“…Hospital anxiety and depression scale (HADS) is a commonly used questionnaire for assessment of depression and anxiety in patients [14,19]. The reliability of this questionnaire has been previous confirmed [20].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, lack of significance with the other used methods may be due to the low number of reported studies. Out of 10 studies reported [1,8,18,19,20,21,22,23,24,25] in the present meta-analysis, six studies [1,18,19,21,23,24] showed a higher significant level of salivary cortisol in the OLP patients compared with the controls.…”
Section: Discussionmentioning
confidence: 63%
“…The studies were published from 2003 to 2017 and included 269 OLP patients and 268 controls. Four studies were reported from India [1,18,19,20], three from the Middle East [21,22,23], two from Europe [24,25], and one from Brazil [8]. In six studies [1,18,21,22,23,24], the detection method of salivary cortisol level was enzyme-linked immunosorbent assay (ELISA), whereas the remaining methods were radioimmunoassay in one study [8] and the chemiluminescence immunoassay in three studies [19,20,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation